Pre-treatment of municipal solid waste incineration (MSWI) bottom ash for utilisation in cement mortar. (15th October 2015) - Saikia, Nabajyoti; Mertens, Gilles; Van Balen, Koenraad; Elsen, Jan; Van Gerven, Tom; Vandecasteele, Carlo
Highlights: Two methods were applied to improve the qualities of two types of municipal solid waste incineration ash samples. Treated ash samples were used as partial replacement of fine aggregate in cement mortar preparation. The adopted methods considerably improved their properties for using as fine aggregate by removing harmful components. The leaching of investigated toxic elements from the cement mortar containing ash samples met the specifications. Abstract: The removal of elemental aluminium, sulphate and harmful organics from two types of MSWI ash samples, the sand sized (0.1–2 mm) fraction of MSWI bottom ash from a grate furnace (SF), and boiler and fly ash from a fluidized bed incinerator (BFA), were done to use as fine aggregates in preparation of cement mortar. Results indicate that the chemical treatment by 0.25 M Na2 CO3 solution can dissolve the Al and the sulphate bearing minerals from the BFA and therefore enhance its quality to use as a fine aggregate in cement mortar preparation. On the other hand, heat treatment at about 675 °C before Na2 CO3 treatment is necessary to improve the quality of SF for using as a fine aggregate. The compressive strengths of mortars improve significantly due to the partial replacement of sand by heat and Na2 CO3 treated ash samples. The proposed treatment methods slightly change the toxic element leaching behaviours of the ash samples. The concentrations of toxic elements in the leachates generated from the treated ash samples as well as the leachates generated from the mortars containing these ash samples are well within the regulatory limits.